Application of chest physiotherapy in toddler patients with pneumonia with ineffective airways clearance: A case study - Rizma Wirza Sriko; Ria Wulandari; Indra Frana Jaya KK; Fitri Afdhal (Indonesian Journal of Health Services, 2024)
Background: Pneumonia is a major respiratory infection that causes inflammation of lung tissue and excessive mucus production, leading to airway obstruction and impaired respiratory function. In toddlers, anatomical and physiological characteristics such as narrow airways and immature immune responses increase the risk of ineffective airway clearance. Effective management strategies are therefore required to facilitate secretion removal and improve respiratory function. Chest physiotherapy is a non-pharmacological intervention widely used to mobilize airway secretions and enhance pulmonary ventilation. Objective: This study aimed to analyze the application of chest physiotherapy in toddler patients with pneumonia experiencing ineffective airway clearance. Methods: This study employed a descriptive analytic case study design conducted in the pediatric inpatient ward of RSUD Siti Fatimah Az-Zahra Hospital, South Sumatra, Indonesia. The study involved two toddler patients aged between 10 months and 2 years who were diagnosed with pneumonia and experienced ineffective airway clearance. Chest physiotherapy was administered twice daily for three consecutive days with a duration of 10–15 minutes per session. Nursing care followed the standard nursing process, including assessment, nursing diagnosis, planning, implementation, and evaluation. Respiratory parameters such as respiratory rate, body temperature, pulse rate, breath sounds, and airway secretion clearance were assessed before and after the intervention. Data were analyzed using descriptive analysis to evaluate changes in respiratory status following chest physiotherapy. Results: Both patients demonstrated clinical improvement after the intervention period. Respiratory rate decreased from 60 to 52 breaths per minute in Patient 1 and from 42 to 40 breaths per minute in Patient 2. Breath sounds such as wheezing gradually disappeared, and airway secretions were expelled more effectively. Pulse rate and body temperature also stabilized during the evaluation period, indicating improved respiratory status and airway clearance. Conclusion: Chest physiotherapy can improve airway clearance and respiratory function in toddlers with pneumonia. This intervention may serve as an effective non-pharmacological nursing strategy to support respiratory management in pediatric pneumonia patients.